Chitin / chitosan aerogel material compounded with biomass calcium carbonate and preparation method of chitin / chitosan aerogel material

By using chitin/chitosan aerogel materials with composite biomass calcium carbonate, the flammability problem of polysaccharide-based aerogel materials is solved, and good flame retardant and mechanical properties are achieved, which is suitable for a variety of high performance application.

CN119431870APending Publication Date: 2025-02-14WUHAN UNIV

Patent Information

Application Number
CN202310954623.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing polypolysaccharide-based aerogel materials have problems with flammability, and the traditional flame retardant addition method increases costs and structural defects, making it difficult to effectively improve its flame retardant performance.

Method used

Using chitin/chitosan aerogel material with complex biomass calcium carbonate, good preparation is prepared by dissolving chitin and biomass calcium carbonate in KOH/urea solution and cross-linking and deacetylation at low temperature. Flame-retardant aerogel material.

Benefits of technology

It achieves low density and good mechanical properties of aerogel materials, while improving its refractory and flame retardant properties, and is suitable for electromagnetic shielding and tissue regeneration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431870A_ABST
    Figure CN119431870A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of macromolecule and aerogel materials, in particular to a chitin / chitosan aerogel material compounded with biomass calcium carbonate and a preparation method of the chitin / chitosan aerogel material. Comprising the following steps: deproteinizing, decoloring, preparing a chitin or chitosan raw material containing biomass calcium carbonate, preparing a biomass calcium carbonate / chitin or biomass calcium carbonate / chitosan solution, and preparing the biomass calcium carbonate / chitin or biomass calcium carbonate / chitosan aerogel material. The raw materials used in the method are wide in source, the content of biomass calcium carbonate is high, good biocompatibility is achieved, no extra filler needs to be added, the utilization rate of marine waste can be increased, and carbon emission generated by removing calcium carbonate and use of chemical reagents are reduced. The aerogel prepared in the invention has low density and good mechanical properties, the fire resistance and mechanical properties of the aerogel are improved, and the aerogel has wide application prospects in the fields of electromagnetic shielding, tissue regeneration and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer and aerogel materials, and in particular to a chitin / chitosan aerogel material of composite biomass calcium carbonate and a preparation method thereof. Background Art

[0002] Since SS Kistler prepared the first SiO2 aerogel by critical point drying in 1931, aerogel, as the material with the lowest density in the world, has always attracted the attention of researchers. Aerogel has the characteristics of high porosity, high specific surface area and low thermal conductivity. Different types of aerogel materials with this function have wide applications in separation adsorption, catalysis, thermal insulation and sound insulation, electromagnetic shielding and energy storage. According to the composition of aerogel, it can be divided into inorganic oxide aerogel, organic aerogel and all-carbon aerogel prepared with macromolecules as carbon source, new carbon nanotube aerogel and graphene aerogel. These aerogel materials generally have problems such as unsustainable raw material acquisition and high energy consumption in the preparation process. In comparison, polysaccharides (cellulose, chitin, chitosan and starch, etc.) as a type of biomacromolecule are widely present in nature. They are favored because of their green raw material source, easy chemical and physical modification, good biocompatibility and environmentally friendly waste treatment. Therefore, polysaccharide-based aerogel materials have become a frontier topic in the current aerogel research field. Polysaccharide-based aerogels are generally highly flammable due to their organic skeletons and huge contact area with the air. In order to improve flame retardancy, the usual method is to add flame retardants to the aerogel by physical mixing or chemical grafting. However, the additional addition of flame retardants will not only introduce defects in the structure, but also increase the preparation cost of the aerogel. The method of filling aerogels with nanoparticles to improve their flame retardancy also faces the problem of easy agglomeration of nanoparticles and difficulty in processing. Calcium carbonate, as an inorganic filler commonly used in the polymer industry, is thermally stable (decomposition temperature exceeds 800°C). Adding it to aerogels can reduce the mass fraction of combustibles and inhibit combustion. At the same time, the addition of calcium carbonate can also become a physical cross-linking point through hydrogen bonding and coordination, thereby improving the mechanical properties of the polysaccharide matrix.

[0003] Among common polysaccharide materials, cellulose is mainly found in plants such as trees, cotton and algae, and usually does not coexist with mineral salts. The main source of chitosan is the shells of animals such as crustaceans and insects. In shrimp and crab shells, in addition to chitosan content of up to 15% to 40%, there is also a large amount of calcium carbonate (20% to 50%) (Nature. 2015, 524, 155-157), which provides convenience for the in-situ use of mineral salts to prepare chitosan composite materials without adding additional inorganic fillers. In the shells of shrimp and crabs, chitosan molecular chains are arranged in reverse parallel to form nanofibers through hydrogen bond self-assembly, and the nanofibers are then wrapped by proteins. These nanofibers are stacked with each other to form a sheet structure, and then stacked with minerals mainly composed of calcium carbonate to form a unique "Bouligand" structure to increase the strength of the shell and effectively resist the impact of external forces (Science. 2013, 339, 773-779). Shrimp and crab shells, these natural marine wastes, can not only be directly used as raw materials for chitin and calcium carbonate, but the unique interaction and multi-level structure between the two also provide practical guidance for subsequent researchers to design high-strength / functionalized organic polymer-inorganic composite materials. Unfortunately, due to the lack of suitable processing methods, the associated biomass calcium carbonate is usually treated as waste in the traditional utilization of chitin in the past. This not only causes a waste of resources, but also uses a large amount of acidic reagents to decompose it into CO2 and soluble calcium salts during the decalcification process, which increases the processing cost while causing a large amount of carbon emissions and serious environmental pollution. In current research, calcium carbonate / chitin-based composite materials are usually prepared by in-situ doping of calcium carbonate in chitin solutions by chemical reactions (Int. J. Biol. Macromol. 2021, 181, 786-792, J. Hazard. Mater. 2022, 423, 127137). This doping method of adding additional calcium carbonate increases the cost, makes the material preparation process cumbersome, and cannot replicate the unique structure and properties formed between biomass inorganic particles and chitin. Converting chitin to chitosan is an important part of the comprehensive utilization of chitin. As a derivative of chitin, when the proportion of amino groups in the C2 position on the chitin molecular chain is greater than 50% to 55%, it becomes chitosan. The presence of amino groups gives the chitosan chain positive charge, making it the only positively charged polysaccharide macromolecule in nature. Chitosan therefore has many special properties, such as antibacterial and adsorbent properties. Furthermore, the physicochemical and biological functions of chitosan-based materials can be regulated by controlling the degree of deacetylation (Adv. Healthcare Mater. 2020, 2000951). Therefore, the comprehensive utilization of biomass calcium carbonate obtained by crustacean biomineralization and chitin itself can simultaneously achieve the purpose of reducing pollution emissions during acid treatment, simplifying material preparation processes, and optimizing material properties.Furthermore, converting the chitin contained in it into chitosan, which has a wide source, low cost, biodegradability and unique physicochemical and biological properties, has high practical significance and research value for the preparation of various structural, biological and functional materials.

[0004] Chitosan is a common biopolysaccharide with a wide range of sources. Its production in nature ranks second only to cellulose, and it has a high potential for utilization. However, due to its inherent high crystallinity and strong intramolecular / intermolecular hydrogen bonding, it cannot be melt-processed by preparing a melt, and it is also difficult to dissolve in most water / organic solvents, thus lacking effective processing methods, and its application field has been limited. In the past hundred years, the only solvents that can effectively dissolve chitosan are inorganic acids, LiCl / DMAc, CaCl2·2H2O / methanol, alkali / urea, low eutectic solvents, ionic liquids, and hexafluoroisopropanol. Compared with chitosan, chitosan has better solubility and can be simply dissolved in acetic acid. In order to retain the crystalline structure of biomass calcium carbonate in chitosan / chitosan raw materials, acetic acid cannot be used, which further narrows the types of solvents that can be selected. Fortunately, NaOH / urea has been proven to successfully dissolve chitosan, but its dissolution process requires multiple freeze-thaw cycles, which is almost worthless for large-scale industrial applications. The KOH system has a better dissolution effect: our research group found that chitin can be efficiently dissolved in a KOH / urea solution after a freeze-thaw cycle (Sci. China. Chem. 2016, 59, 1405-1414), and first reported a method for rapid dissolution of chitin in a KOH / urea system (CN1030593220B), as well as an efficient dissolution method for chitin in a KOH ice-water solution system (CN114907577A). Biomass calcium carbonate is chemically inert to the alkaline environment of the solution in the alkaline solvent system, and can effectively maintain the original crystal structure of biomass calcium carbonate. As a universal dissolution method, the KOH system can also efficiently dissolve chitosan. At the same time, the presence of strong alkali in the system can achieve in-situ deacetylation of chitosan solution, thereby eliminating the conversion link in the preparation process of chitosan raw materials, avoiding the large-scale use of additional alkali, and realizing the deep utilization of the solvent system, meeting the concept of improving atomic utilization in "green chemistry", and further reducing energy consumption. Therefore, this efficient and rapid dissolution method makes it possible to industrialize chitin and chitosan materials on a large scale, with low pollution and low cost. Therefore, on this basis, developing an effective comprehensive utilization and conversion method of raw materials containing biomass calcium carbonate / chitin (chitosan) has far-reaching significance for the subsequent functionalization of chitin composite materials.

[0005] In summary, a comprehensive utilization method suitable for calcium-containing chitin is found, including the purification, dissolution, conversion and aerogel material preparation method of biomass calcium carbonate, chitin and chitosan in suitable raw materials, so as to more effectively utilize biomass resources such as shrimp and crab shells. It not only improves the resource utilization rate, but also further improves the comprehensive performance of existing polysaccharide-based aerogel materials, which is in line with the environmental protection concept of "turning harm into benefit and turning waste into treasure" of the country, government and industry. Summary of the invention

[0006] One of the purposes of the present invention is to provide a method for preparing a chitin / chitosan aerogel material composited with biomass calcium carbonate, wherein the solvent system used can efficiently dissolve and utilize chitin and biomass calcium carbonate, the alkali contained in the solvent will not react with calcium carbonate, the alkali and stabilizer used are recyclable, low in pollution, and has the potential for large-scale industrial application.

[0007] The second object of the present invention is to provide a chitin / chitosan aerogel material composited with biomass calcium carbonate, wherein the solvent system used can efficiently dissolve and utilize chitin and biomass calcium carbonate, the alkali contained in the solvent will not react with calcium carbonate, the alkali and stabilizer used are recyclable, low in pollution, and has the potential for large-scale industrial application.

[0008] The solution adopted by the present invention to achieve one of the purposes is: a method for preparing a chitin / chitosan aerogel material composited with biomass calcium carbonate, comprising the following steps:

[0009] S1. Take an alkaline aqueous solution of a certain concentration and soak the chitosan raw material containing biomass calcium carbonate at a certain material-liquid ratio to remove the protein in the raw material;

[0010] S2, taking a certain amount of bleaching agent, soaking and stirring the deproteinized raw material at a certain material-liquid ratio to remove the pigment in the raw material, washing and drying after treatment;

[0011] S3, taking an alkaline aqueous solution of a certain concentration, soaking and stirring the depigmented raw material at a certain material-liquid ratio to partially deacetylate, washing and drying after treatment, to obtain a chitin raw material containing biomass calcium carbonate with a deacetylation degree of not more than 50%, or a chitosan raw material containing biomass calcium carbonate with a deacetylation degree of more than 50%;

[0012] S4, preparing the pretreated raw materials into a certain concentration of biomass calcium carbonate / chitin or biomass calcium carbonate / chitosan solution, the dissolution method includes any one of the following methods: A1, taking a certain concentration of KOH aqueous solution, adding a certain amount of stabilizer and pretreated raw materials, mixing evenly and freezing until completely frozen, then thawing and dissolving to obtain a chitosan or chitosan solution containing biomass calcium carbonate, centrifuging and degassing for standby use; A2, taking a certain concentration of KOH aqueous solution, adding a certain amount of stabilizer and pretreated raw materials, stirring above the freezing point and below 0°C to completely dissolve the chitosan or chitosan raw materials containing biomass calcium carbonate, obtaining a chitosan or chitosan solution containing biomass calcium carbonate, centrifuging and degassing for standby use;

[0013] A3, take a certain concentration of KOH aqueous solution, precool it, add a certain amount of pretreated raw materials, place it at a certain temperature for a period of time, add a certain amount of ice cubes or ice water and stir until it is completely dissolved to obtain a chitin or chitosan solution containing biomass calcium carbonate, centrifuge and degas, and then set aside;

[0014] S5, preparing biomass calcium carbonate / chitin or biomass calcium carbonate / chitosan aerogel material, including any one of the following methods: B1, adding a certain amount of cross-linking agent to the calcium carbonate / chitin or chitosan solution obtained in step S4 at a certain feed ratio, stirring evenly at a temperature lower than the gelation temperature of the solution, centrifuging for degassing, and then standing to form, washing and regenerating after forming to obtain biomass calcium carbonate / chitin or biomass calcium carbonate / chitosan hydrogel; completely freezing the obtained hydrogel at low temperature, and freeze-drying to obtain biomass calcium carbonate / chitin or biomass calcium carbonate / chitosan aerogel material; B2, placing the calcium carbonate / chitin or chitosan solution obtained in step S4 at a temperature higher than the gelation temperature of the solution The obtained hydrogel is completely frozen at low temperature and freeze-dried to obtain biomass calcium carbonate / chitin or biomass calcium carbonate / chitosan aerogel material; B3, a certain amount of cross-linking agent is added to the calcium carbonate / chitin or chitosan solution obtained in step S4 at a certain feed ratio, and the mixture is stirred evenly at a temperature lower than the gelation temperature of the solution, and then centrifuged for degassing, and then allowed to stand for molding, and the molding is washed and regenerated to obtain biomass calcium carbonate / chitin or biomass calcium carbonate / chitosan hydrogel; a certain concentration of tert-butanol is used to replace the solvent of the hydrogel, and the obtained tert-butanol gel is completely replaced at After being completely frozen at low temperature, washing, and drying at room temperature to obtain biomass calcium carbonate / chitin or biomass calcium carbonate / chitosan aerogel material; B4, adding a certain amount of cross-linking agent to the biomass calcium carbonate / chitin solution obtained in step S4 at a certain feed ratio, stirring evenly at a certain temperature and then centrifuging for degassing, chemically cross-linking, in-situ deacetylation and molding at a certain temperature, washing and regenerating after molding, to obtain biomass calcium carbonate / chitosan hydrogel; after completely freezing the obtained hydrogel at low temperature, freeze-drying to obtain biomass calcium carbonate / chitosan aerogel material; B5, placing the biomass calcium carbonate / chitosan solution obtained in step S4 at a certain temperature for in-situ deacetylation and molding, washing and regenerating after molding , obtain biomass calcium carbonate / chitosan hydrogel; completely freeze the obtained hydrogel at low temperature, and freeze-dry to obtain biomass calcium carbonate / chitosan aerogel material; B6, add a certain amount of cross-linking agent to the biomass calcium carbonate / chitin solution obtained in step S4 at a certain feed ratio, stir evenly at a temperature lower than the gelation temperature of the solution, and then centrifuge for degassing, deacetylate in situ at a certain temperature after chemical cross-linking and shape, wash and regenerate after shaping to obtain biomass calcium carbonate / chitosan hydrogel; use a certain concentration of tert-butanol to replace the solvent of the hydrogel, and after complete replacement, completely freeze the obtained tert-butanol gel at low temperature, wash, and dry at room temperature to obtain biomass calcium carbonate / chitosan aerogel material;Preparation of chitosan-based aerogel material by heterogeneous deacetylation of biomass calcium carbonate / chitin solution: B7, adding a certain amount of crosslinking agent to the biomass calcium carbonate / chitin solution obtained in step S4 at a certain feed ratio, stirring evenly at a temperature lower than the gelation temperature of the solution, centrifuging for degassing, and then standing to form, washing and regenerating after forming to obtain biomass calcium carbonate / chitin hydrogel; subjecting the obtained hydrogel to heterogeneous deacetylation in an alkaline aqueous solution of a certain concentration to obtain a biomass calcium carbonate / chitosan hydrogel; after completely freezing at low temperature, freeze-drying to obtain a biomass calcium carbonate / chitosan aerogel material; B8, placing the biomass calcium carbonate / chitosan solution obtained in step S4 at a temperature slightly higher than the gelation temperature of the solution to standing to form, washing and regenerating after forming to obtain a biomass calcium carbonate / chitosan hydrogel; After a heterogeneous deacetylation reaction in an alkaline aqueous solution of a certain concentration, a biomass calcium carbonate / chitosan hydrogel is obtained, which is completely frozen at low temperature and freeze-dried to obtain a biomass calcium carbonate / chitosan aerogel material; B9, a certain amount of crosslinking agent is added to the biomass calcium carbonate / chitosan solution obtained in step S4 at a certain feed ratio, and the mixture is stirred evenly at a temperature lower than the gelation temperature of the solution, and then centrifuged for degassing, and then allowed to stand for molding, and after molding, it is washed and regenerated to obtain a biomass calcium carbonate / chitosan hydrogel, and the obtained hydrogel is subjected to a heterogeneous deacetylation reaction in an alkaline aqueous solution of a certain concentration to obtain a biomass calcium carbonate / chitosan hydrogel, and a certain concentration of tert-butyl alcohol is used to perform solvent replacement on the hydrogel, and after complete replacement, the obtained tert-butyl alcohol gel is completely frozen at low temperature, washed, and dried at room temperature to obtain a biomass calcium carbonate / chitosan aerogel material. ;

[0015] Preferably, in step S1, the chitosan raw materials containing biomass calcium carbonate are shrimp, crab and chitosan-rich mollusk shells.

[0016] Preferably, in step S1, the alkaline aqueous solution is a NaOH aqueous solution, a KOH aqueous solution or a mixed aqueous solution of NaOH and KOH, the total mass fraction of the alkali in the solution is 4wt% to 30wt%, and the material-liquid ratio of the chitosan raw material containing biomass calcium carbonate to the alkaline aqueous solution is 1:10 to 100.

[0017] Preferably, in step S2, the bleaching agent is an aqueous solution of at least one of H2O2, sodium perborate, peracetic acid, and hydrosulfite, the mass fraction of the aqueous solution is 1:10-30, and the material-liquid ratio of the raw material to the bleaching agent aqueous solution is 1:10-100.

[0018] Preferably, in step S3, the alkaline aqueous solution is NaOH or KOH solution, the mass fraction is 30wt% to 50wt%, the material-liquid ratio of the raw material to the alkaline aqueous solution is 1:10 to 100, the temperature is 60°C to 170°C, and the biomass calcium carbonate / chitin or chitosan raw material is obtained by controlling the deacetylation degree.

[0019] Preferably, in step S4, the concentration of chitin or chitosan in the solution in methods A1 to A3 is 1wt% to 10wt%; the mass fraction of the KOH aqueous solution in methods A1 and A2 is 5wt% to 30wt%, the stabilizer is at least one of urea, thiourea and polyethylene glycol, and the concentration of the stabilizer in the solution is 0 to 20wt%, the mass fraction of the KOH aqueous solution in method A3 is 30wt% to 60wt%, and the mass fraction of the KOH aqueous solution is reduced to 5wt% to 30wt% after adding ice cubes or ice water.

[0020] Preferably, in step S5, the crosslinking agent used in method B1 is one of epoxy compounds, glycidyl ether compounds, acrylates or aldehyde compounds, and the molar ratio of the crosslinking agent to the sugar unit of chitin or chitosan in the solution is 0.4:1 to 4.0:1; the stirring temperature is -25°C to 5°C.

[0021] Preferably, in step S5, the gelation temperature in method B2 is 30° C. to 50° C.; and the concentration of tert-butanol in method B3 is 10 wt % to 70 wt %.

[0022] Preferably, in step S5, the temperature of the in-situ deacetylation in methods B4 to B6 is 60 to 170° C., and the deacetylation time is 2 h to 48 h; in methods B7 to B9, the alkaline aqueous solution in the heterogeneous deacetylation is a NaOH aqueous solution or a KOH aqueous solution, the concentration of the alkaline aqueous solution is 30 wt % to 50 wt %, the reaction temperature is 60 to 170° C., and the reaction is cycled 1 to 5 times.

[0023] The solution adopted by the present invention to achieve the second purpose is: the aerogel material is prepared by the preparation method, and has a porous structure, is composed of chitin or chitosan, and contains calcium carbonate.

[0024] The present invention has the following advantages and beneficial effects:

[0025] (1) The raw materials used in the present invention are widely available, have a high content of biomass calcium carbonate, and have good biocompatibility. In situ utilization of calcium carbonate does not require the addition of additional fillers. The comprehensive utilization of biomass calcium carbonate and chitin can increase the utilization rate of marine waste and reduce the carbon emissions and use of chemical reagents generated by the removal of calcium carbonate.

[0026] (2) The solvent system used in the present invention can efficiently dissolve and utilize chitin, chitosan and biomass calcium carbonate. The alkali contained in the solvent will not react with calcium carbonate. The alkali and stabilizer used are recyclable, low in pollution, and has the potential for large-scale industrial application.

[0027] (3) The biomass calcium carbonate / chitin (chitosan) aerogel prepared in the present invention has low density and good mechanical properties. The chitin aerogel itself has good biocompatibility. The use of biomass calcium carbonate improves the fire resistance and mechanical properties of the aerogel. Biomass calcium carbonate / chitin (chitosan) aerogel has broad application prospects in the fields of electromagnetic shielding, tissue regeneration, etc.

[0028] (4) The solvent system used in the present invention can achieve in-situ deacetylation of chitosan solution, so that it can be converted into chitosan at low cost and become a stable solution, which has obvious application advantages. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a sample picture of biomass calcium carbonate / chitin aerogel prepared in an embodiment of the present invention;

[0030] Figure 2 This is a scanning electron microscope image of the cross section of the biomass calcium carbonate / chitin aerogel prepared in Example 1 of the present invention;

[0031] Figure 3 This is a scanning electron microscope image of the cross section of the biomass calcium carbonate / chitin aerogel prepared in Example 2 of the present invention;

[0032] Figure 4 This is a scanning electron microscope image of the cross section of the biomass calcium carbonate / chitin aerogel prepared in Example 3 of the present invention;

[0033] Figure 5 This is the XRD pattern of the biomass calcium carbonate / chitin aerogel prepared in the embodiment of the present invention;

[0034] Figure 6 The combustion test results of aerogel materials prepared in Example 1 of the present invention and the comparative example are shown in Figure 1, wherein (a) shows the combustion test diagram of chitin aerogel, and (b) shows the combustion test result of Example 1. DETAILED DESCRIPTION

[0035] For a better understanding of the present invention, the following examples are provided to further illustrate the present invention, but the present invention is not limited to the following examples.

[0036] <Example 1>

[0037] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. The pretreated raw material was uniformly stirred with the precooled 50wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes were added to dilute the KOH concentration to 20wt% and stirred quickly until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and ethylene glycol diglycidyl ether was added as a cross-linking agent, and the molar ratio of the cross-linking agent to the chitin sugar unit was 1.8:1. After stirring evenly, centrifugal degassing was performed, poured into a well plate, and the bubbles were removed again by shaking, and then placed at 5°C for 84 hours to form. After forming, it was placed in deionized water to wash out ions and regenerate to obtain biomass calcium carbonate / chitin hydrogel, and the hydrogel was freeze-dried to obtain biomass calcium carbonate / chitin aerogel material.

[0038] Aerogel sample picture Figure 1 As shown, other embodiments have similar morphologies.

[0039] The surface of the aerogel material was observed using a scanning electron microscope (SEM, Sigma, Zeiss Germany). Figure 2 As shown, the sample exhibits a uniform porous structure.

[0040] The crystal structures of chitin and biomass calcium carbonate in aerogels were analyzed using an X-ray diffractometer (XRD, SmartLab 9kW, Rigaku Japan). Figure 5 As shown in the figure, the characteristic peaks of chitosan (020) (021) exist but are not obvious. This may be due to the existence of chemical cross-linking areas between chitosan chains, which makes the chitosan crystallization peak weak. The crystallization peak of calcium carbonate can be clearly observed in the figure. According to the peak position, it can be concluded that there are three crystal forms of calcium carbonate in the sample, namely calcite, vaterite and aragonite. This shows that the alkali treatment, dissolution process and subsequent preparation process will not destroy the structure of biomass calcium carbonate, so that it can be completely preserved in the aerogel.

[0041] <Example 2>

[0042] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. The pretreated raw material was uniformly stirred with the precooled 50wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes were added to dilute the KOH concentration to 20wt% and stirred rapidly until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and epichlorohydrin was added dropwise as a crosslinking agent, and the molar ratio of the crosslinking agent to the chitin sugar unit was 2.4:1. After stirring evenly, centrifuge to degas, pour into a well plate, shake to remove bubbles again, and place at 5°C for 84 hours to form. After forming, place in deionized water to wash and regenerate to obtain biomass calcium carbonate / chitin hydrogel, and freeze-dry the hydrogel to obtain biomass calcium carbonate / chitin aerogel material.

[0043] The surface of the aerogel material was observed using a scanning electron microscope (SEM, Sigma, Zeiss Germany). Figure 3 As shown, the sample exhibits a uniform porous structure.

[0044] <Example 3>

[0045] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. The pretreated raw material was uniformly stirred with the pre-cooled 50wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes were added to dilute the KOH concentration to 20wt% and stirred rapidly until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and glutaraldehyde was added dropwise as a cross-linking agent, and the molar ratio of the cross-linking agent to the chitin sugar unit was 3.0:1. After stirring evenly, centrifuge to degas, pour into a well plate, shake to remove bubbles again, and place at 5°C for 84 hours to form. After forming, place in deionized water to wash and regenerate to obtain biomass calcium carbonate / chitin hydrogel, and freeze-dry the hydrogel to obtain biomass calcium carbonate / chitin aerogel material.

[0046] The surface of the aerogel material was observed using a scanning electron microscope (SEM, Sigma, Zeiss Germany). Figure 4 As shown, the sample exhibits a uniform porous structure.

[0047] <Example 4>

[0048] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. The pretreated raw material was uniformly stirred with the precooled 50wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes were added to dilute the KOH concentration to 20wt% and stirred quickly until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and ethylene glycol diglycidyl ether was added as a cross-linking agent, and the molar ratio of the cross-linking agent to the chitin sugar unit was 1.2:1. After stirring evenly, centrifugal degassing was performed, poured into a well plate, and the bubbles were removed again by shaking, and then placed at 5°C for 72 hours to form. After forming, it was placed in deionized water to wash out ions and regenerate to obtain biomass calcium carbonate / chitin hydrogel, and the hydrogel was freeze-dried to obtain biomass calcium carbonate / chitin aerogel material.

[0049] The crystal structures of chitin and biomass calcium carbonate in aerogels were analyzed using an X-ray diffractometer (XRD, SmartLab 9kW, Rigaku Japan). Figure 5 The results are similar to those shown in Example 1.

[0050] <Example 5>

[0051] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. The pretreated raw material was uniformly stirred with the precooled 50wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes were added to dilute the KOH concentration to 20wt% and stirred quickly until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and ethylene glycol diglycidyl ether was added as a cross-linking agent, with a molar ratio of the cross-linking agent to the chitin sugar unit of 1.8:1. After stirring evenly, the solution was centrifuged and degassed, poured into a well plate, shaken to remove bubbles again, and placed at 5°C for 72 hours to form. After forming, the solution was placed in deionized water to wash away ions and regenerate to obtain a biomass calcium carbonate / chitin hydrogel, and the hydrogel was freeze-dried to obtain a biomass calcium carbonate / chitin aerogel material.

[0052] <Example 6>

[0053] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. The pretreated raw material was uniformly stirred with the precooled 50wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes were added to dilute the KOH concentration to 20wt% and stirred quickly until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and ethylene glycol diglycidyl ether was added as a cross-linking agent, with a molar ratio of the cross-linking agent to the chitin sugar unit of 2.4:1. After stirring evenly, the solution was centrifuged and degassed, poured into a well plate, shaken to remove bubbles again, and placed at 5°C for 72 hours to form. After forming, the solution was placed in deionized water to wash away ions and regenerate to obtain a biomass calcium carbonate / chitin hydrogel, and the hydrogel was freeze-dried to obtain a biomass calcium carbonate / chitin aerogel material.

[0054] The crystal structures of chitin and biomass calcium carbonate in aerogels were analyzed using an X-ray diffractometer (XRD, SmartLab 9kW, Rigaku Japan). Figure 5 The results are similar to those shown in Example 1.

[0055] <Example 7>

[0056] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. The pretreated raw material was uniformly stirred with the precooled 50wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes were added to dilute the KOH concentration to 20wt% and stirred quickly until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and ethylene glycol diglycidyl ether was added as a cross-linking agent, with a molar ratio of the cross-linking agent to the chitin sugar unit of 3.0:1. After stirring evenly, the solution was centrifuged and degassed, poured into a well plate, shaken to remove bubbles again, and placed at 5°C for 72 hours to form. After forming, the solution was placed in deionized water to wash away ions and regenerate to obtain a biomass calcium carbonate / chitin hydrogel, and the hydrogel was freeze-dried to obtain a biomass calcium carbonate / chitin aerogel material.

[0057] The crystal structures of chitin and biomass calcium carbonate in aerogels were analyzed using an X-ray diffractometer (XRD, SmartLab 9kW, Rigaku Japan). Figure 5 The results are similar to those shown in Example 1.

[0058] <Example 8>

[0059] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. The pretreated raw material was uniformly stirred with the precooled 50wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes were added to dilute the KOH concentration to 20wt% and stirred quickly until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and ethylene glycol diglycidyl ether was added as a cross-linking agent, and the molar ratio of the cross-linking agent to the chitin sugar unit was 3.8:1. After stirring evenly, centrifugal degassing was performed, poured into a well plate, and the bubbles were removed again by shaking, and then placed at 5°C for 72 hours to form. After forming, it was placed in deionized water to wash out ions and regenerate to obtain biomass calcium carbonate / chitin hydrogel, and the hydrogel was freeze-dried to obtain biomass calcium carbonate / chitin aerogel material.

[0060] The crystal structures of chitin and biomass calcium carbonate in aerogels were analyzed using an X-ray diffractometer (XRD, SmartLab 9kW, Rigaku Japan). Figure 5 The results are similar to those shown in Example 1.

[0061] <Example 9>

[0062] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. The pretreated raw material was uniformly stirred with the precooled 50wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes were added to dilute the KOH concentration to 20wt% and stirred rapidly until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and adipaldehyde was added dropwise as a crosslinking agent, and the molar ratio of the crosslinking agent to the chitin sugar unit was 2.4:1. After stirring evenly, centrifuge to degas, pour into a well plate, shake to remove bubbles again, and place at 5°C for 84 hours to form. After forming, place in deionized water to wash and regenerate to obtain biomass calcium carbonate / chitin hydrogel, and freeze-dry the hydrogel to obtain biomass calcium carbonate / chitin aerogel material.

[0063] <Example 10>

[0064] The crab shell raw material containing calcium carbonate is immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio is 1:15, and the deproteinization treatment is carried out at room temperature for 24h, and the treatment is repeated twice and then washed. The deproteinized raw material is immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio is 1:15, the pH is adjusted to 9, and the decolorization is carried out at 80°C for 45min, and the treatment is washed and dried. The decolorized raw material is immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio is 1:15, and the deacetylation is carried out at 80°C for 1h, and the treatment is washed, dried and crushed. A certain amount of pretreated raw material and urea are added to a 14wt% KOH solution precooled to 0°C, and the mass fraction of urea is 7wt%. Stir rapidly at a temperature below 0°C and above the freezing point until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and ethylene glycol diglycidyl ether was added as a cross-linking agent, and the molar ratio of the cross-linking agent to the chitin sugar unit was 1.4:1. After stirring evenly, centrifugal degassing was performed, poured into a well plate, and the bubbles were removed again by shaking, and then placed at 5°C for 72 hours to form. After forming, it was placed in deionized water to wash out ions and regenerate to obtain biomass calcium carbonate / chitin hydrogel, and the hydrogel was freeze-dried to obtain biomass calcium carbonate / chitin aerogel material.

[0065] <Example 11>

[0066] The crab shell raw material containing calcium carbonate is immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio is 1:15, and the deproteinization treatment is carried out at room temperature for 24h, and the treatment is repeated twice and then washed. The deproteinized raw material is immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio is 1:15, the pH is adjusted to 9, and the decolorization is carried out at 80°C for 45min, and the treatment is washed and dried. The decolorized raw material is immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio is 1:15, and the deacetylation is carried out at 80°C for 1h, and the treatment is washed, dried and crushed. A certain amount of pretreated raw material and urea are added to a 16wt% KOH solution precooled to 0°C, and the mass fraction of urea is 9wt%. Stir rapidly at a temperature below 0°C and above the freezing point until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and 1,6-hexanediol diglycidyl ether was added as a cross-linking agent, and the molar ratio of the cross-linking agent to the chitin sugar unit was 2.2:1. After stirring evenly, centrifugal degassing was performed, poured into a well plate, and the bubbles were removed again by shaking, and then placed at 5°C for 72 hours to form. After forming, it was placed in deionized water to wash out ions and regenerate to obtain biomass calcium carbonate / chitin hydrogel, and the hydrogel was freeze-dried to obtain biomass calcium carbonate / chitin aerogel material.

[0067] <Example 12>

[0068] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. A certain amount of pretreated raw material and urea were added to a 18wt% KOH solution precooled to 0°C, and the mass fraction of urea was 9wt%. Stir rapidly at 0°C or above the freezing point until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and epichlorohydrin was added dropwise as a crosslinking agent, and the molar ratio of the crosslinking agent to the chitin sugar unit was 3.0:1. After stirring evenly, centrifuge to degas, pour into a well plate, shake to remove bubbles again, and place at 5°C for 72 hours to form. After forming, place in deionized water to wash and regenerate to obtain biomass calcium carbonate / chitin hydrogel, and freeze-dry the hydrogel to obtain biomass calcium carbonate / chitin aerogel material.

[0069] <Example 13>

[0070] The crab shell raw material containing calcium carbonate is immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio is 1:15, and the deproteinization treatment is carried out at room temperature for 24h, and the treatment is repeated twice and then washed. The deproteinized raw material is immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio is 1:15, the pH is adjusted to 9, and the decolorization is carried out at 80°C for 45min, and the treatment is washed and dried. The decolorized raw material is immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio is 1:15, and the deacetylation is carried out at 80°C for 1h, and the treatment is washed, dried and crushed. A certain amount of pretreated raw material and urea are added to a 18wt% KOH solution precooled to 0°C, and the mass fraction of urea is 9wt%. Stir rapidly at 0°C or above the freezing point until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and propylene glycol triglycidyl ether was added as a cross-linking agent, with a molar ratio of the cross-linking agent to the chitin sugar unit of 4.0:1. After stirring evenly, the solution was centrifuged and degassed, poured into a well plate, shaken to remove bubbles again, and placed at 5°C for 72 hours to form. After forming, the solution was placed in deionized water to wash away ions and regenerate to obtain a biomass calcium carbonate / chitin hydrogel, and the hydrogel was freeze-dried to obtain a biomass calcium carbonate / chitin aerogel material.

[0071] <Example 14>

[0072] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. A certain amount of pretreated raw material and urea were added to a 16wt% KOH solution, and the mass fraction of urea was 8wt%. It was placed at a certain temperature to freeze and freeze, and then thawed to obtain a 7wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and pentaerythritol tetraglycidyl ether was added dropwise as a crosslinking agent, and the molar ratio of the crosslinking agent to the chitin sugar unit was 1.6:1. After stirring evenly, centrifuge to degas, pour into a well plate, shake to remove bubbles again, and place at 5°C for 72 hours to form. After forming, place in deionized water to wash and regenerate to obtain biomass calcium carbonate / chitin hydrogel, and freeze-dry the hydrogel to obtain biomass calcium carbonate / chitin aerogel material.

[0073] <Example 15>

[0074] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80℃ for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80℃ for 1h, and the treatment was washed, dried and crushed. A certain amount of pretreated raw material and urea were added to the 16wt% KOH solution, and the mass fraction of urea was 8wt%. It was placed at a certain temperature to freeze and freeze, and then thawed to obtain a 7wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15℃ and polyethylene glycol diacrylate was added dropwise as a crosslinking agent, and the molar ratio of the crosslinking agent to the chitin sugar unit was 3.2:1. After stirring evenly, centrifuge to degas, pour into a well plate, shake to remove bubbles again, and place at 5°C for 72 hours to form. After forming, place in deionized water to wash and regenerate to obtain biomass calcium carbonate / chitin hydrogel, and freeze-dry the hydrogel to obtain biomass calcium carbonate / chitin aerogel material.

[0075] <Example 16>

[0076] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. The pretreated raw material was uniformly stirred with the precooled 50wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes were added to dilute the KOH concentration to 20wt% and stirred quickly until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and ethylene glycol diglycidyl ether was added dropwise as a crosslinker, the molar ratio of the crosslinker to the chitin sugar unit was 1.2:1, and the solution was placed at 5°C for 48 hours to form. After forming, the solution was placed in deionized water to wash out ions and regenerate to obtain a biomass calcium carbonate / chitin hydrogel, and 70wt% tert-butanol was used to replace the solvent of the hydrogel. After complete replacement, the obtained tert-butanol gel was completely frozen at low temperature, washed in deionized water, and dried at room temperature to obtain a biomass calcium carbonate / chitin aerogel material.

[0077] <Example 17>

[0078] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 50wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. A certain amount of pretreated raw material and urea were added to a 18wt% KOH solution precooled to 0°C, and the mass fraction of urea was 9wt%. Stir rapidly at 0°C or above the freezing point until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and epichlorohydrin was added dropwise as a crosslinking agent, and the molar ratio of the crosslinking agent to the chitin sugar unit was 3.0:1. After stirring evenly, centrifuge to degas, pour into a well plate, shake to remove bubbles again, and place at 5°C for 72 hours to form. After forming, place in deionized water to wash and regenerate to obtain biomass calcium carbonate / chitin hydrogel, and freeze-dry the hydrogel to obtain biomass calcium carbonate / chitin aerogel material.

[0079] <Example 18>

[0080] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. The pretreated raw material was uniformly stirred with the precooled 50wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes were added to dilute the KOH concentration to 20wt% and stirred quickly until completely dissolved to obtain a 7.5wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and polyethylene glycol diacrylate was added as a crosslinker, with a molar ratio of the crosslinker to the chitin sugar unit of 3.0:1. After stirring evenly, the solution was centrifuged for degassing, poured into a well plate, and shaken to remove bubbles again. After chemical crosslinking for 1 hour, the solution was in situ deacetylated at 60°C for 48 hours to form. After forming, the solution was placed in deionized water for deionization and regenerated to obtain a biomass calcium carbonate / chitosan hydrogel, and the hydrogel was freeze-dried to obtain a biomass calcium carbonate / chitosan aerogel material.

[0081] <Example 19>

[0082] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80℃ for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 60wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80℃ for 1h, and the treatment was washed, dried and crushed. A certain amount of pretreated raw material and urea were added to the 16.5wt% KOH solution, and the mass fraction of urea was 10wt%. It was placed at a certain temperature to freeze and freeze, and then thawed to obtain a 5wt% biomass calcium carbonate / chitosan solution. After centrifugal degassing, the solution was stirred at -15℃ and ethylene glycol diglycidyl ether was added as a crosslinking agent, and the molar ratio of the crosslinking agent to the chitosan sugar unit was 2.2:1. After stirring evenly, centrifuge to degas, pour into a well plate, shake to remove bubbles again, and place at 5°C for 72 hours to form. After forming, place in deionized water to wash and regenerate to obtain biomass calcium carbonate / chitosan hydrogel, and freeze-dry the hydrogel to obtain biomass calcium carbonate / chitosan aerogel material.

[0083] <Example 20>

[0084] The crab shell raw material containing calcium carbonate is immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio is 1:15, and the deproteinization treatment is carried out at room temperature for 24h, and the treatment is repeated twice and then washed. The deproteinized raw material is immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio is 1:15, the pH is adjusted to 9, and the decolorization is carried out at 80°C for 45min, and the treatment is washed and dried. The decolorized raw material is immersed in a 60wt% KOH aqueous solution and stirred, wherein the material-liquid ratio is 1:15, and the deacetylation is carried out at 80°C for 1h, and the treatment is washed, dried and crushed. A certain amount of pretreated raw material and urea are added to a 16.5wt% KOH solution precooled to 0°C, and the mass fraction of urea is 5wt%. Stir rapidly at 0°C or above the freezing point until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitosan solution. After centrifugal degassing, the solution is stirred at -15°C and glutaraldehyde is added dropwise as a crosslinking agent, and the molar ratio of the crosslinking agent to the chitosan sugar unit is 4.0:1. After stirring evenly, centrifuge to degas, pour into a well plate, shake to remove bubbles again, and place at 5°C for 72 hours to form. After forming, place in deionized water to wash and regenerate to obtain biomass calcium carbonate / chitosan hydrogel, and freeze-dry the hydrogel to obtain biomass calcium carbonate / chitosan aerogel material.

[0085] <Example 21>

[0086] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. The pretreated raw material was uniformly stirred with the precooled 45wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes were added to dilute the KOH concentration to 16.5wt% and stirred quickly until completely dissolved to obtain an 8wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and propylene glycol triglycidyl ether was added as a crosslinker, and the molar ratio of the crosslinker to the chitin sugar unit was 4.0:1. After stirring evenly, the solution was centrifuged and degassed, poured into a well plate, and shaken to remove bubbles again. After chemical crosslinking for 2 hours, it was placed in deionized water to wash and regenerate to obtain biomass calcium carbonate / chitin hydrogel. The obtained hydrogel was subjected to heterogeneous deacetylation in a 60wt% NaOH aqueous solution for 6 hours and repeated 3 times, and the reaction temperature was 80°C. The biomass calcium carbonate / chitosan hydrogel was obtained; 70wt% tert-butanol was used to replace the solvent of the hydrogel, and after complete replacement, the obtained tert-butanol gel was completely frozen at low temperature, washed in deionized water, and dried at room temperature to obtain the biomass calcium carbonate / chitosan aerogel material.

[0087] <Example 22>

[0088] The crab shell raw material containing calcium carbonate is immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio is 1:15, and the deproteinization treatment is carried out at room temperature for 24h, and the treatment is repeated twice and then washed. The deproteinized raw material is immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio is 1:15, the pH is adjusted to 9, and the decolorization is carried out at 80°C for 45min, and the treatment is washed and dried. The decolorized raw material is immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio is 1:15, and the deacetylation is carried out at 80°C for 1h, and the treatment is washed, dried and crushed. A certain amount of pretreated raw material and urea are added to a 16.5wt% KOH solution, and the mass fraction of urea is 20wt%. It is placed at a certain temperature to freeze and then thaw to obtain a 5wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and adipaldehyde was added dropwise as a crosslinking agent, the molar ratio of the crosslinking agent to the chitosan unit was 3.0:1, and the solution was placed at 5°C for 48 hours to form. After forming, the solution was placed in deionized water to wash out ions and regenerate to obtain a biomass calcium carbonate / chitin hydrogel, and the obtained hydrogel was subjected to a heterogeneous deacetylation reaction in a 50wt% KOH solution for 4 hours and repeated twice, the reaction temperature was 110°C, and the biomass calcium carbonate / chitosan hydrogel was obtained; 70wt% tert-butanol was used to replace the solvent of the hydrogel, and after complete replacement, the obtained tert-butanol gel was completely frozen at low temperature, washed in deionized water, and dried at room temperature to obtain a biomass calcium carbonate / chitosan aerogel material.

[0089] <Example 23>

[0090] The crab shell raw material containing calcium carbonate is immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio is 1:15, and the deproteinization treatment is carried out at room temperature for 24h, and the treatment is repeated twice and then washed. The deproteinized raw material is immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio is 1:15, the pH is adjusted to 9, and the decolorization is carried out at 80°C for 45min, and the treatment is washed and dried. The decolorized raw material is immersed in a 60wt% KOH aqueous solution and stirred, wherein the material-liquid ratio is 1:15, and the deacetylation is carried out at 80°C for 1h, and the treatment is washed, dried and crushed. A certain amount of pretreated raw material and urea are added to a 30wt% KOH solution precooled to 0°C, and the mass fraction of urea is 10wt%. Stir rapidly at 0°C or above the freezing point until completely dissolved to obtain a 10wt% biomass calcium carbonate / chitosan solution. The pretreated raw material was uniformly stirred with the precooled 50wt% KOH aqueous solution, placed at 5°C for 4h, and then ice cubes were added to dilute the KOH concentration to 30wt% and quickly stirred until completely dissolved to obtain a 10wt% biomass calcium carbonate / chitosan solution. After centrifugal degassing, the solution was stirred at -15°C and epichlorohydrin was added dropwise as a crosslinking agent, and the molar ratio of the crosslinking agent to the chitosan sugar unit was 0.4:1. After stirring evenly, centrifugal degassing was performed, poured into a perforated plate, shaken to remove bubbles again, and placed at 5°C for 72h to form. After forming, it was placed in deionized water to wash and regenerate to obtain a biomass calcium carbonate / chitosan hydrogel, and the hydrogel was freeze-dried to obtain a biomass calcium carbonate / chitosan aerogel material.

[0091] <Example 24>

[0092] The crab shell raw material containing calcium carbonate is immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio is 1:15, and the deproteinization treatment is carried out at room temperature for 24h, and the treatment is repeated twice and then washed. The deproteinized raw material is immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio is 1:15, the pH is adjusted to 9, and the decolorization is carried out at 80°C for 45min, and the treatment is washed and dried. The decolorized raw material is immersed in a 60wt% KOH aqueous solution and stirred, wherein the material-liquid ratio is 1:15, and the deacetylation is carried out at 80°C for 1h, and the treatment is washed, dried and crushed. The pretreated raw material is uniformly stirred with the pre-cooled 45wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes are added to dilute the KOH concentration to 16.5wt% and stirred rapidly until completely dissolved to obtain an 8wt% biomass calcium carbonate / chitosan solution. After centrifugal degassing, the solution is stirred at -15°C and glutaraldehyde is added dropwise as a cross-linking agent, and the molar ratio of the cross-linking agent to the chitosan sugar unit is 4.0:1. After stirring evenly, centrifuge to degas, pour into a well plate, shake to remove bubbles again, and place at 5°C for 72 hours to form. After forming, place in deionized water to wash and regenerate to obtain biomass calcium carbonate / chitosan hydrogel, and freeze-dry the hydrogel to obtain biomass calcium carbonate / chitosan aerogel material.

[0093] <Example 25>

[0094] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. The pretreated raw material was uniformly stirred with the precooled 50wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes were added to dilute the KOH concentration to 20wt% and stirred quickly until completely dissolved to obtain a 9wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and polyglycerol diglycidyl ether was added as a cross-linking agent, the molar ratio of the cross-linking agent to the chitin sugar unit was 1.2:1, and after chemical cross-linking for 5 hours, it was in situ deacetylated at 100°C for 48 hours and formed. After forming, it was placed in deionized water to wash deions and regenerate to obtain biomass calcium carbonate / chitosan hydrogel, and the hydrogel was solvent replaced with 40wt% tert-butanol. After complete replacement, the obtained tert-butanol gel was completely frozen at low temperature, placed in deionized water for washing, and dried at room temperature to obtain biomass calcium carbonate / chitosan aerogel material.

[0095] <Example 26>

[0096] The crab shell raw material containing calcium carbonate is immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio is 1:15, and the deproteinization treatment is carried out at room temperature for 24h, and the treatment is repeated twice and then washed. The deproteinized raw material is immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio is 1:15, the pH is adjusted to 9, and the decolorization is carried out at 80°C for 45min, and the treatment is washed and dried. The decolorized raw material is immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio is 1:15, and the deacetylation is carried out at 80°C for 1h, and the treatment is washed, dried and crushed. A certain amount of pretreated raw material and urea are added to a 10wt% KOH solution precooled to 0°C, and the mass fraction of urea is 8wt%. Stir rapidly at 0°C or above the freezing point until completely dissolved to obtain an 8wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and polyethylene glycol diacrylate was added dropwise as a crosslinking agent, and the molar ratio of the crosslinking agent to the chitin sugar unit was 3.0:1. After stirring evenly, the solution was centrifuged and degassed, poured into a well plate, and shaken to remove bubbles again. After chemical crosslinking for 5 hours, it was placed in deionized water to wash out ions and regenerate to obtain biomass calcium carbonate / chitin hydrogel. The obtained hydrogel was subjected to heterogeneous deacetylation in a 30wt% KOH aqueous solution for 6 hours and repeated 5 times, and the reaction temperature was 120°C. Biomass calcium carbonate / chitosan hydrogel was obtained; after molding, it was placed in deionized water to wash out ions and regenerate to obtain biomass calcium carbonate / chitosan hydrogel, and the hydrogel was freeze-dried to obtain biomass calcium carbonate / chitosan aerogel material.

[0097] <Example 27>

[0098] The crab shell raw material containing calcium carbonate is immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio is 1:15, and the deproteinization treatment is carried out at room temperature for 24h, and the treatment is repeated twice and then washed. The deproteinized raw material is immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio is 1:15, the pH is adjusted to 9, and the decolorization is carried out at 80°C for 45min, and the treatment is washed and dried. The decolorized raw material is immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio is 1:15, and the deacetylation is carried out at 80°C for 1h, and the treatment is washed, dried and crushed. A certain amount of pretreated raw material and urea are added to a 16.5wt% KOH solution precooled to 0°C, and the mass fraction of urea is 5wt%. Stir rapidly at 0°C or above the freezing point until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and ethylene glycol diglycidyl ether was added as a crosslinker, with a molar ratio of crosslinker to chitin sugar unit of 2.4:1. After stirring evenly, the mixture was centrifuged and degassed, poured into a well plate, and shaken to remove bubbles again. After chemical crosslinking for 24 hours, the mixture was placed in deionized water to wash out ions and regenerate to obtain biomass calcium carbonate / chitin hydrogel. The obtained hydrogel was subjected to heterogeneous deacetylation in a 50wt% NaOH aqueous solution for 6 hours at a reaction temperature of 170°C. The biomass calcium carbonate / chitosan hydrogel was obtained; 45wt% tert-butanol was used to replace the solvent of the hydrogel, and after complete replacement, the obtained tert-butanol gel was completely frozen at low temperature, washed in deionized water, and dried at room temperature to obtain biomass calcium carbonate / chitosan aerogel material.

[0099] <Example 28>

[0100] The crab shell raw material containing calcium carbonate is immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio is 1:15, and the deproteinization treatment is carried out at room temperature for 24h, and the treatment is repeated twice and then washed. The deproteinized raw material is immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio is 1:15, the pH is adjusted to 9, and the decolorization is carried out at 80°C for 45min, and the treatment is washed and dried. The decolorized raw material is immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio is 1:15, and the deacetylation is carried out at 80°C for 1h, and the treatment is washed, dried and crushed. A certain amount of pretreated raw material and urea are added to a 30wt% KOH solution precooled to 0°C, and the mass fraction of urea is 10wt%. Stir rapidly at a temperature below 0°C and above the freezing point until completely dissolved to obtain a 10wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and glutaraldehyde was added dropwise as a crosslinking agent, the molar ratio of the crosslinking agent to the chitin sugar unit was 3.0:1, and the solution was placed at 5°C for 48 hours to form. After forming, the solution was placed in deionized water to wash out ions and regenerate to obtain a biomass calcium carbonate / chitin hydrogel, and the obtained hydrogel was subjected to a heterogeneous deacetylation reaction in a 30wt% NaOH solution for 2 hours and repeated 4 times, the reaction temperature was 70°C, and the biomass calcium carbonate / chitosan hydrogel was obtained; 60wt% tert-butanol was used to replace the solvent of the hydrogel, and after complete replacement, the obtained tert-butanol gel was completely frozen at low temperature, placed in deionized water for washing, and dried at room temperature to obtain a biomass calcium carbonate / chitosan aerogel material.

[0101] <Example 29>

[0102] The crab shell raw material containing calcium carbonate is immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio is 1:15, and the deproteinization treatment is carried out at room temperature for 24h, and the treatment is repeated twice and then washed. The deproteinized raw material is immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio is 1:15, the pH is adjusted to 9, and the decolorization is carried out at 80°C for 45min, and the treatment is washed and dried. The decolorized raw material is immersed in a 60wt% KOH aqueous solution and stirred, wherein the material-liquid ratio is 1:15, and the deacetylation is carried out at 80°C for 1h, and the treatment is washed, dried and crushed. A certain amount of pretreated raw material and urea are added to a 16.5wt% KOH solution, and the mass fraction of urea is 20wt%. It is placed at a certain temperature and frozen, and then thawed to obtain a 5wt% biomass calcium carbonate / chitosan solution. After centrifugal degassing, the solution was stirred at -15°C and polyethylene glycol diacrylate was added dropwise as a crosslinking agent, the molar ratio of the crosslinking agent to the chitosan sugar unit was 1.2:1, and the solution was placed at 5°C for 48 hours to form. After forming, the solution was placed in deionized water to wash out ions and regenerate to obtain a biomass calcium carbonate / chitosan hydrogel, and 10wt% tert-butanol was used to replace the solvent of the hydrogel. After complete replacement, the obtained tert-butanol gel was completely frozen at low temperature, washed in deionized water, and dried at room temperature to obtain a biomass calcium carbonate / chitosan aerogel material.

[0103] <Example 30>

[0104] The crab shell raw material containing calcium carbonate is immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio is 1:15, and the deproteinization treatment is carried out at room temperature for 24h, and the treatment is repeated twice and then washed. The deproteinized raw material is immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio is 1:15, the pH is adjusted to 9, and the decolorization is carried out at 80°C for 45min, and the treatment is washed and dried. The decolorized raw material is immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio is 1:15, and the deacetylation is carried out at 80°C for 1h, and the treatment is washed, dried and crushed. A certain amount of pretreated raw material and urea are added to a 12wt% KOH solution precooled to 0°C, and the mass fraction of urea is 7wt%. Stir rapidly at 0°C or above the freezing point until completely dissolved to obtain a 6wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and ethylene glycol diglycidyl ether was added as a cross-linking agent, the molar ratio of the cross-linking agent to the chitin sugar unit was 2.2:1, and after chemical cross-linking for 5 hours, it was in situ deacetylated at 170°C for 4 hours and formed. After forming, it was placed in deionized water to wash away ions and regenerate to obtain biomass calcium carbonate / chitosan hydrogel, and 70wt% of tert-butanol was used to replace the solvent of the hydrogel. After complete replacement, the obtained tert-butanol gel was completely frozen at low temperature, placed in deionized water for washing, and dried at room temperature to obtain biomass calcium carbonate / chitosan aerogel material.

[0105] <Example 31>

[0106] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. A certain amount of pretreated raw material and urea were added to the 12wt% KOH solution, and the mass fraction of urea was 8wt%. It was placed at a certain temperature to freeze and freeze, and then thawed to obtain a 4wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and pentaerythritol tetraglycidyl ether was added dropwise as a crosslinking agent, and the molar ratio of the crosslinking agent to the chitin sugar unit was 0.8:1. After stirring evenly, centrifuge to degas, pour into a well plate, shake to remove bubbles again, chemically cross-link for 5 hours, and then in-situ deacetylate at 120°C for 24 hours to form. After forming, place in deionized water to wash and regenerate to obtain biomass calcium carbonate / chitosan hydrogel, and freeze-dry the hydrogel to obtain biomass calcium carbonate / chitosan aerogel material.

[0107] <Example 32>

[0108] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, where the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, where the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80℃ for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, where the material-liquid ratio was 1:15, and the deacetylation was carried out at 80℃ for 1h, and the treatment was washed, dried and crushed. A certain amount of pretreated raw material was added to the 30wt% KOH solution. It was placed at a certain temperature to freeze and freeze, and then thawed to obtain a 5wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15℃ and 1,4-butanediol diglycidyl ether was added dropwise as a crosslinker, and the molar ratio of the crosslinker to the chitin sugar unit was 1:1. After stirring evenly, centrifuge to degas, pour into a well plate, shake to remove bubbles again, chemically cross-link for 5 hours, and then deacetylate in situ at 170°C for 2 hours to form. After forming, place in deionized water to wash and regenerate to obtain biomass calcium carbonate / chitosan hydrogel, and freeze-dry the hydrogel to obtain biomass calcium carbonate / chitosan aerogel material.

[0109] <Example 33>

[0110] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. The pretreated raw material was uniformly stirred with the precooled 30wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes were added to dilute the KOH concentration to 5wt% and stirred quickly until completely dissolved to obtain a 2wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and glutaraldehyde was added dropwise as a crosslinking agent, the molar ratio of the crosslinking agent to the chitosan unit was 1.6:1, and the solution was placed at 5°C for 48 hours to form. After forming, the solution was placed in deionized water to wash out ions and regenerate to obtain a biomass calcium carbonate / chitin hydrogel, and the obtained hydrogel was subjected to a heterogeneous deacetylation reaction in a 60wt% NaOH solution for 2 hours at a reaction temperature of 140°C to obtain a biomass calcium carbonate / chitosan hydrogel; 30wt% tert-butanol was used to replace the solvent of the hydrogel, and after complete replacement, the obtained tert-butanol gel was completely frozen at low temperature, washed in deionized water, and dried at room temperature to obtain a biomass calcium carbonate / chitosan aerogel material.

[0111] <Example 34>

[0112] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 60wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. The pretreated raw material was uniformly stirred with the precooled 30wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes were added to dilute the KOH concentration to 20wt% and stirred quickly until completely dissolved to obtain a 1wt% biomass calcium carbonate / chitosan solution. After centrifugal degassing, the solution was stirred at -15°C and adipaldehyde was added dropwise as a crosslinking agent, the molar ratio of the crosslinking agent to the chitosan unit was 1.8:1, and the solution was placed at 5°C for 48 hours to form. After forming, the solution was placed in deionized water to wash out ions and regenerate to obtain a biomass calcium carbonate / chitosan hydrogel, and the hydrogel was solvent replaced with 40wt% tert-butanol. After complete replacement, the obtained tert-butanol gel was completely frozen at low temperature, washed in deionized water, and dried at room temperature to obtain a biomass calcium carbonate / chitosan aerogel material.

[0113] <Example 35>

[0114] The crab shell raw material containing calcium carbonate is immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio is 1:15, and the deproteinization treatment is carried out at room temperature for 24h, and the treatment is repeated twice and then washed. The deproteinized raw material is immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio is 1:15, the pH is adjusted to 9, and the decolorization is carried out at 80°C for 45min, and the treatment is washed and dried. The decolorized raw material is immersed in a 60wt% KOH aqueous solution and stirred, wherein the material-liquid ratio is 1:15, and the deacetylation is carried out at 80°C for 1h, and the treatment is washed, dried and crushed. A certain amount of pretreated raw material and urea are added to the 11.0wt% KOH solution, and the mass fraction of urea is 4.8wt%. It is placed at a certain temperature to freeze and then thaw to obtain a 7wt% biomass calcium carbonate / chitosan solution. After centrifugal degassing, the solution was stirred at -15°C and 1,6-hexanediol diglycidyl ether was added dropwise as a crosslinker, the molar ratio of the crosslinker to the chitosan unit was 2.6:1, and the solution was placed at 5°C for 48 hours to form. After forming, the solution was placed in deionized water to wash out ions and regenerate to obtain a biomass calcium carbonate / chitosan hydrogel, and the hydrogel was solvent-replaced with 70wt% tert-butanol. After complete replacement, the obtained tert-butanol gel was completely frozen at low temperature, washed in deionized water, and dried at room temperature to obtain a biomass calcium carbonate / chitosan aerogel material.

[0115] <Example 36>

[0116] The crab shell raw material containing calcium carbonate is immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio is 1:15, and the deproteinization treatment is carried out at room temperature for 24h, and the treatment is repeated twice and then washed. The deproteinized raw material is immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio is 1:15, the pH is adjusted to 9, and the decolorization is carried out at 80°C for 45min, and the treatment is washed and dried. The decolorized raw material is immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio is 1:15, and the deacetylation is carried out at 80°C for 1h, and the treatment is washed, dried and crushed. A certain amount of pretreated raw material and urea are added to a 9.5wt% KOH solution, and the mass fraction of urea is 8wt%. It is placed at a certain temperature to freeze and then thaw to obtain a 4wt% biomass calcium carbonate / chitin solution. After centrifugal degassing, the solution was stirred at -15°C and epichlorohydrin was added dropwise as a cross-linking agent, the molar ratio of the cross-linking agent to the chitin sugar unit was 2.4:1, and after chemical cross-linking for 2 hours, it was in situ deacetylated at 60°C for 36 hours and formed. After forming, it was placed in deionized water to wash away ions and regenerate to obtain a biomass calcium carbonate / chitosan hydrogel. After forming, it was placed in deionized water to wash away ions and regenerate to obtain a biomass calcium carbonate / chitosan hydrogel. The hydrogel was freeze-dried to obtain a biomass calcium carbonate / chitosan aerogel material.

[0117] <Example 37>

[0118] The crab shell raw material containing calcium carbonate is immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio is 1:15, and the deproteinization treatment is carried out at room temperature for 24h, and the treatment is repeated twice and then washed. The deproteinized raw material is immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio is 1:15, the pH is adjusted to 9, and the decolorization is carried out at 80°C for 45min, and the treatment is washed and dried. The decolorized raw material is immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio is 1:15, and the deacetylation is carried out at 80°C for 1h, and the treatment is washed, dried and crushed. A certain amount of pretreated raw material and urea are added to a 16.5wt% KOH solution, and the mass fraction of urea is 10wt%. It is placed at a certain temperature to freeze and then thaw to obtain a 5wt% biomass calcium carbonate / chitin solution. The solution was cast into a film on a glass plate by a casting method, and was placed at 50°C for standing to form. After forming, it was placed in deionized water to wash out ions and regenerate to obtain a biomass calcium carbonate / chitosan hydrogel; the obtained hydrogel was subjected to a heterogeneous deacetylation reaction in a 60wt% KOH solution for 2h at a reaction temperature of 160°C to obtain a biomass calcium carbonate / chitosan hydrogel; after being completely frozen at low temperature, freeze-dried to obtain a biomass calcium carbonate / chitosan aerogel material; the tensile strength was 11.7MPa, the fracture strain was 20%, and the Young's modulus was 298MPa.

[0119] <Example 38>

[0120] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 60wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. The pretreated raw material was uniformly stirred with the precooled 30wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes were added to dilute the KOH concentration to 5wt% and stirred quickly until completely dissolved to obtain a 1wt% biomass calcium carbonate / chitosan solution. The solution was cast into a film on a glass plate by a casting method, and then placed at 40°C for static molding. After molding, it was placed in deionized water for deionization and regeneration to obtain a biomass calcium carbonate / chitosan hydrogel; after being completely frozen at low temperature, it was freeze-dried to obtain a biomass calcium carbonate / chitosan aerogel material; the tensile strength was 0.7MPa, the fracture strain was 3%, and the Young's modulus was 60MPa.

[0121] <Example 39>

[0122] The crab shell raw material containing calcium carbonate is immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio is 1:15, and the deproteinization treatment is carried out at room temperature for 24h, and the treatment is repeated twice and then washed. The deproteinized raw material is immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio is 1:15, the pH is adjusted to 9, and the decolorization is carried out at 80°C for 45min, and the treatment is washed and dried. The decolorized raw material is immersed in a 60wt% KOH aqueous solution and stirred, wherein the material-liquid ratio is 1:15, and the deacetylation is carried out at 80°C for 1h, and the treatment is washed, dried and crushed. A certain amount of pretreated raw material and urea are added to a 30wt% KOH solution, and the mass fraction of urea is 0wt%. It is placed at a certain temperature to freeze and freeze, and then thawed to obtain a 1wt% biomass calcium carbonate / chitosan solution. The solution was cast into a film on a glass plate by a casting method, and was placed at 30°C to form a film. After forming, it was placed in deionized water to wash away ions and regenerate to obtain a biomass calcium carbonate / chitosan hydrogel; after being completely frozen at low temperature, it was freeze-dried to obtain a biomass calcium carbonate / chitosan aerogel material; the tensile strength was 0.5MPa, the breaking strain was 5%, and the Young's modulus was 35MPa.

[0123] <Example 40>

[0124] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. The pretreated raw material was uniformly stirred with the precooled 50wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes were added to dilute the KOH concentration to 30wt% and stirred quickly until completely dissolved to obtain a 10wt% biomass calcium carbonate / chitin solution. The solution was cast into a film on a glass plate by a casting method, and was placed at 55°C for static molding. After molding, it was placed in deionized water to wash out ions and regenerate to obtain a biomass calcium carbonate / chitin hydrogel; the obtained hydrogel was subjected to a heterogeneous deacetylation reaction in a 45wt% NaOH solution for 6h and repeated twice, and the reaction temperature was 60°C to obtain a biomass calcium carbonate / chitosan hydrogel; after being completely frozen at low temperature, freeze-dried to obtain a biomass calcium carbonate / chitosan aerogel material; the tensile strength was 18.4MPa, the fracture strain was 19%, and the Young's modulus was 624MPa.

[0125] <Example 41>

[0126] The crab shell raw material containing calcium carbonate is immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio is 1:15, and the deproteinization treatment is carried out at room temperature for 24h, and the treatment is repeated twice and then washed. The deproteinized raw material is immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio is 1:15, the pH is adjusted to 9, and the decolorization is carried out at 80°C for 45min, and the treatment is washed and dried. The decolorized raw material is immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio is 1:15, and the deacetylation is carried out at 80°C for 1h, and the treatment is washed, dried and crushed. A certain amount of pretreated raw material and urea are added to the 11.2wt% KOH solution, and the mass fraction of urea is 4wt%. It is placed at a certain temperature to freeze and freeze, and then thawed to obtain a 5wt% biomass calcium carbonate / chitin solution. The solution was cast into a film on a glass plate by a casting method, placed at 80°C for in-situ deacetylation for 10 hours and formed, and after forming, placed in deionized water for deionization and regeneration to obtain a biomass calcium carbonate / chitosan hydrogel; the obtained hydrogel was completely frozen at low temperature and freeze-dried to obtain a biomass calcium carbonate / chitosan aerogel material; the tensile strength was 8.3MPa, the fracture strain was 23%, and the Young's modulus was 309MPa.

[0127] <Example 42>

[0128] The crab shell raw material containing calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. The pretreated raw material was uniformly stirred with the precooled 50wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes were added to dilute the KOH concentration to 20wt% and stirred quickly until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitin solution. The solution was cast into a film on a glass plate by a casting method, placed at 45°C for static molding, and then placed in deionized water for deionization and regeneration to obtain a biomass calcium carbonate / chitin hydrogel; the hydrogel was freeze-dried to obtain a biomass calcium carbonate / chitin aerogel material. The tensile strength was 13.4MPa, the breaking strain was 26%, and the Young's modulus was 431MPa.

[0129] <Example 43>

[0130] The crab shell raw material containing calcium carbonate is immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio is 1:15, and the deproteinization treatment is carried out at room temperature for 24h, and the treatment is repeated twice and then washed. The deproteinized raw material is immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio is 1:15, the pH is adjusted to 9, and the decolorization is carried out at 80°C for 45min, and the treatment is washed and dried. The decolorized raw material is immersed in a 60wt% KOH aqueous solution and stirred, wherein the material-liquid ratio is 1:15, and the deacetylation is carried out at 80°C for 1h, and the treatment is washed, dried and crushed. A certain amount of pretreated raw material and urea are added to a 11.2wt% KOH solution precooled to 0°C, and the mass fraction of urea is 4wt%. Stir rapidly at a temperature below 0°C and above the freezing point until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitosan solution. The solution was cast into a film on a glass plate by a casting method, placed at 50°C for static molding, placed in deionized water for deionization and regeneration after molding to obtain a biomass calcium carbonate / chitosan hydrogel; placed in deionized water for deionization and regeneration after molding to obtain a biomass calcium carbonate / chitosan hydrogel, and the hydrogel was solvent replaced with 10wt% tert-butyl alcohol. After complete replacement, the obtained tert-butyl alcohol gel was completely frozen at low temperature, washed in deionized water, and dried at room temperature to obtain a biomass calcium carbonate / chitosan aerogel material. The tensile strength is 9.4MPa, the breaking strain is 17%, and the Young's modulus is 251MPa.

[0131] <Example 44>

[0132] The crab shell raw material containing calcium carbonate is immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio is 1:15, and the deproteinization treatment is carried out at room temperature for 24h, and the treatment is repeated twice and then washed. The deproteinized raw material is immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio is 1:15, the pH is adjusted to 9, and the decolorization is carried out at 80°C for 45min, and the treatment is washed and dried. The decolorized raw material is immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio is 1:15, and the deacetylation is carried out at 80°C for 1h, and the treatment is washed, dried and crushed. A certain amount of pretreated raw material and urea are added to a 11.2wt% KOH solution precooled to 0°C, and the mass fraction of urea is 4wt%. Stir rapidly at 0°C or above the freezing point until completely dissolved to obtain a 7wt% biomass calcium carbonate / chitin solution. The solution was cast into a film on a glass plate by a casting method, and was placed at 40°C for standing to form. After forming, it was placed in deionized water to wash out ions and regenerate to obtain a biomass calcium carbonate / chitosan hydrogel; the obtained hydrogel was subjected to a heterogeneous deacetylation reaction in a 35wt% KOH solution for 8h and repeated twice, and the reaction temperature was 80°C to obtain a biomass calcium carbonate / chitosan hydrogel; after being completely frozen at low temperature, freeze-dried to obtain a biomass calcium carbonate / chitosan aerogel material; the tensile strength was 8.1MPa, the fracture strain was 16%, and the Young's modulus was 368MPa.

[0133] The density, mechanical properties and other characteristics of the calcium carbonate / chitin (chitosan) aerogel materials prepared in Examples 1 to 36 were respectively characterized, and the test results are shown in Table 1.

[0134] Table 1 Density of the examples and compression strength when the deformation reaches 80%

[0135]

[0136]

[0137] <Comparative Example 1>

[0138] The chitin raw material without calcium carbonate was immersed in a 5.3wt% NaOH aqueous solution, wherein the material-liquid ratio was 1:15, and the deproteinization treatment was carried out at room temperature for 24h, and the treatment was repeated twice and then washed. The deproteinized raw material was immersed in a 1wt% H2O2 aqueous solution and stirred, wherein the material-liquid ratio was 1:15, the pH was adjusted to 9, and the decolorization was carried out at 80°C for 45min, and the treatment was washed and dried. The decolorized raw material was immersed in a 30wt% KOH aqueous solution and stirred, wherein the material-liquid ratio was 1:15, and the deacetylation was carried out at 80°C for 1h, and the treatment was washed, dried and crushed. The pretreated raw material was uniformly stirred with the precooled 50wt% KOH aqueous solution, and after being placed at 5°C for 4h, ice cubes were added to dilute the KOH concentration to 20wt% and stirred rapidly until completely dissolved to obtain a 7wt% chitin solution. After centrifugal degassing, the solution was stirred at -15°C and ethylene glycol diglycidyl ether was added dropwise as a crosslinking agent, and the molar ratio of the crosslinking agent to the chitin sugar unit was 1.8:1. After stirring evenly, centrifuge to degas, pour into a well plate, shake to remove bubbles again, and place at 5°C for 84 hours to form. After forming, place in deionized water to wash and regenerate to obtain biomass calcium carbonate / chitin hydrogel, and freeze-dry the hydrogel to obtain chitin aerogel material.

[0139] The aerogel materials prepared in Example 1 and Comparative Example 1 were subjected to combustion tests respectively. The combustion test results are shown in FIG. Figure 6As shown, (a) shows the combustion test diagram of chitin aerogel. It can be seen from the figure that it is highly flammable due to its rich pore structure and huge specific surface area in contact with air. (b) shows the combustion test results of Example 1. Compared with Comparative Example 1, the open flame of Example 1 reaches the maximum within 2s after ignition, but it is obvious that the flame intensity is significantly weaker than the flame intensity of Comparative Example 1 without biomass calcium carbonate. The open flame of Example 1 disappears at 5s, and the burning time t<5s. The self-extinguishing of the material is achieved in a short time. At the same time, the surface of the material is not burned, and the original structure is retained. The chitin aerogel without biomass calcium carbonate is completely carbonized after 10s of ignition. This is because the presence of non-combustible biomass calcium carbonate acts as a thermal barrier, blocking the spread of heat. At the same time, the non-combustible gas CO2 produced by its partial decomposition further isolates oxygen, so that the material can be self-extinguished in a short time after ignition without falling. The vertical combustion experiment proves that the prepared biomass calcium carbonate / chitin aerogel material has good flame retardant and fire resistant properties.

[0140] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.

Claims

1. A method for preparing a chitin / chitosan aerogel material composited with biomass calcium carbonate, characterized in that: The following steps are involved: S1. Take an alkaline aqueous solution of a certain concentration and soak the chitosan raw material containing biomass calcium carbonate at a certain material-liquid ratio to remove the protein in the raw material; S2, taking a certain amount of bleaching agent, soaking and stirring the deproteinized raw material at a certain material-liquid ratio to remove the pigment in the raw material, washing and drying after treatment; S3, taking an alkaline aqueous solution of a certain concentration, soaking and stirring the depigmented raw material at a certain material-liquid ratio to partially deacetylate, washing and drying after treatment, to obtain a chitin raw material containing biomass calcium carbonate with a deacetylation degree of not more than 50%, or a chitosan raw material containing biomass calcium carbonate with a deacetylation degree of more than 50%; S4, the pretreated raw materials are formulated into a certain concentration of biomass calcium carbonate / chitin or biomass calcium carbonate / chitosan solution, and the dissolution method includes any one of the following methods: A1, take a certain concentration of KOH aqueous solution, add a certain amount of stabilizer and pretreated raw materials, mix well and freeze until completely frozen, then thaw and dissolve to obtain a chitosan or chitosan solution containing biomass calcium carbonate, and centrifuge and degas for standby use; A2, take a certain concentration of KOH aqueous solution, add a certain amount of stabilizer and pretreated raw materials, stir above the freezing point and below 0°C to completely dissolve the chitosan or chitosan raw materials containing biomass calcium carbonate, and obtain a chitosan or chitosan solution containing biomass calcium carbonate, and centrifuge and degas for standby use; A3, take a certain concentration of KOH aqueous solution, precool, add a certain amount of pretreated raw materials, place at a certain temperature for a period of time, add a certain amount of ice cubes or ice water and stir until completely dissolved, to obtain a chitosan or chitosan solution containing biomass calcium carbonate, and centrifuge and degas for standby use; S5, preparing biomass calcium carbonate / chitin or biomass calcium carbonate / chitosan aerogel material, including any one of the following methods: B1, adding a certain amount of cross-linking agent to the calcium carbonate / chitin or chitosan solution obtained in step S4 at a certain feed ratio, stirring evenly at a temperature lower than the gelation temperature of the solution, centrifuging for degassing, and then standing to form, washing and regenerating after forming to obtain biomass calcium carbonate / chitin or biomass calcium carbonate / chitosan hydrogel; completely freezing the obtained hydrogel at low temperature, and freeze-drying to obtain biomass calcium carbonate / chitin or biomass calcium carbonate / chitosan aerogel material; B2, placing the calcium carbonate / chitin or chitosan solution obtained in step S4 at a temperature higher than the gelation temperature of the solution The obtained hydrogel is completely frozen at low temperature and freeze-dried to obtain biomass calcium carbonate / chitin or biomass calcium carbonate / chitosan aerogel material; B3, a certain amount of cross-linking agent is added to the calcium carbonate / chitin or chitosan solution obtained in step S4 at a certain feed ratio, and the mixture is stirred evenly at a temperature lower than the gelation temperature of the solution, and then centrifuged for degassing, and then allowed to stand for molding, and the molding is washed and regenerated to obtain biomass calcium carbonate / chitin or biomass calcium carbonate / chitosan hydrogel; a certain concentration of tert-butanol is used to replace the solvent of the hydrogel, and the obtained tert-butanol gel is completely replaced at After being completely frozen at low temperature, washing, and drying at room temperature to obtain biomass calcium carbonate / chitin or biomass calcium carbonate / chitosan aerogel material; B4, adding a certain amount of cross-linking agent to the biomass calcium carbonate / chitin solution obtained in step S4 at a certain feed ratio, stirring evenly at a certain temperature and then centrifuging for degassing, chemically cross-linking, in-situ deacetylation and molding at a certain temperature, washing and regenerating after molding, to obtain biomass calcium carbonate / chitosan hydrogel; after completely freezing the obtained hydrogel at low temperature, freeze-drying to obtain biomass calcium carbonate / chitosan aerogel material; B5, placing the biomass calcium carbonate / chitosan solution obtained in step S4 at a certain temperature for in-situ deacetylation and molding, washing and regenerating after molding , obtain biomass calcium carbonate / chitosan hydrogel; completely freeze the obtained hydrogel at low temperature, and freeze-dry to obtain biomass calcium carbonate / chitosan aerogel material; B6, add a certain amount of cross-linking agent to the biomass calcium carbonate / chitin solution obtained in step S4 at a certain feed ratio, stir evenly at a temperature lower than the gelation temperature of the solution, and then centrifuge for degassing, deacetylate in situ at a certain temperature after chemical cross-linking and shape, wash and regenerate after shaping to obtain biomass calcium carbonate / chitosan hydrogel; use a certain concentration of tert-butanol to replace the solvent of the hydrogel, and after complete replacement, completely freeze the obtained tert-butanol gel at low temperature, wash, and dry at room temperature to obtain biomass calcium carbonate / chitosan aerogel material;Preparation of chitosan-based aerogel material by heterogeneous deacetylation of biomass calcium carbonate / chitin solution: B7, adding a certain amount of crosslinking agent to the biomass calcium carbonate / chitin solution obtained in step S4 at a certain feed ratio, stirring evenly at a temperature lower than the gelation temperature of the solution, centrifuging for degassing, and then standing to form, washing and regenerating after forming to obtain biomass calcium carbonate / chitin hydrogel; subjecting the obtained hydrogel to heterogeneous deacetylation in an alkaline aqueous solution of a certain concentration to obtain a biomass calcium carbonate / chitosan hydrogel; after completely freezing at low temperature, freeze-drying to obtain a biomass calcium carbonate / chitosan aerogel material; B8, placing the biomass calcium carbonate / chitosan solution obtained in step S4 at a temperature slightly higher than the gelation temperature of the solution to standing to form, washing and regenerating after forming to obtain a biomass calcium carbonate / chitosan hydrogel; After a heterogeneous deacetylation reaction in an alkaline aqueous solution of a certain concentration, a biomass calcium carbonate / chitosan hydrogel is obtained, which is completely frozen at low temperature and freeze-dried to obtain a biomass calcium carbonate / chitosan aerogel material; B9, a certain amount of crosslinking agent is added to the biomass calcium carbonate / chitosan solution obtained in step S4 at a certain feed ratio, and the mixture is stirred evenly at a temperature lower than the gelation temperature of the solution, and then centrifuged for degassing, and then allowed to stand for molding, and after molding, it is washed and regenerated to obtain a biomass calcium carbonate / chitosan hydrogel, and the obtained hydrogel is subjected to a heterogeneous deacetylation reaction in an alkaline aqueous solution of a certain concentration to obtain a biomass calcium carbonate / chitosan hydrogel, and a certain concentration of tert-butyl alcohol is used to perform solvent replacement on the hydrogel, and after complete replacement, the obtained tert-butyl alcohol gel is completely frozen at low temperature, washed, and dried at room temperature to obtain a biomass calcium carbonate / chitosan aerogel material. ; 2. The method for preparing the chitin / chitosan aerogel material of composite biomass calcium carbonate according to claim 1, characterized in that: In the step S1, the chitosan raw materials containing biomass calcium carbonate are shrimp, crab and chitosan-rich mollusk shells.

3. The method for preparing the chitin / chitosan aerogel material of composite biomass calcium carbonate according to claim 1, characterized in that: In step S1, the alkaline aqueous solution is a NaOH aqueous solution, a KOH aqueous solution or a mixed aqueous solution of NaOH and KOH, the total mass fraction of the alkali in the solution is 4wt% to 30wt%, and the material-liquid ratio of the chitosan raw material containing biomass calcium carbonate to the alkaline aqueous solution is 1:10 to 100.

4. The method for preparing the chitin / chitosan aerogel material of composite biomass calcium carbonate according to claim 1, characterized in that: In the step S2, the bleaching agent is an aqueous solution of at least one of H2O2, sodium perborate, peracetic acid, and hydrosulfite, the mass fraction of the aqueous solution is 1:10-30, and the material-liquid ratio of the raw material to the bleaching agent aqueous solution is 1:10-100.

5. The method for preparing the chitin / chitosan aerogel material of composite biomass calcium carbonate according to claim 1, characterized in that: In step S3, the alkaline aqueous solution is NaOH or KOH solution, the mass fraction is 30wt% to 50wt%, the material-liquid ratio of the raw material to the alkaline aqueous solution is 1:10 to 100, the temperature is 60°C to 170°C, and the biomass calcium carbonate / chitin or chitosan raw material is obtained by controlling the deacetylation degree.

6. The method for preparing chitin / chitosan aerogel material of composite biomass calcium carbonate according to claim 1, characterized in that: In step S4, the concentration of chitosan or chitosan in the solution in methods A1 to A3 is 1wt% to 10wt%; the mass fraction of the KOH aqueous solution in methods A1 and A2 is 5wt% to 30wt%, the stabilizer is at least one of urea, thiourea and polyethylene glycol, the concentration of the stabilizer in the solution is 0 to 20wt%, the mass fraction of the KOH aqueous solution in method A3 is 30wt% to 60wt%, and the mass fraction of the KOH aqueous solution is reduced to 5wt% to 30wt% after adding ice cubes or ice water.

7. The method for preparing chitin / chitosan aerogel material of composite biomass calcium carbonate according to claim 1, characterized in that: In step S5, the crosslinking agent used in method B1 is one of epoxy compounds, glycidyl ether compounds, acrylates or aldehyde compounds, and the molar ratio of the crosslinking agent to the sugar unit of chitin or chitosan in the solution is 0.4:1 to 4.0:1; the stirring temperature is -25°C to 5°C.

8. The method for preparing chitin / chitosan aerogel material of composite biomass calcium carbonate according to claim 1, characterized in that: In step S5, the gelation temperature in method B2 is 30° C. to 50° C.; the concentration of tert-butyl alcohol in method B3 is 10 wt % to 70 wt %.

9. The method for preparing chitin / chitosan aerogel material of composite biomass calcium carbonate according to claim 1, characterized in that: In step S5, the temperature of the in-situ deacetylation in methods B4 to B6 is 60 to 170° C., and the deacetylation time is 2 h to 48 h; in methods B7 to B9, the alkaline aqueous solution in the heterogeneous deacetylation is a NaOH aqueous solution or a KOH aqueous solution, the concentration of the alkaline aqueous solution is 30 wt % to 50 wt %, the reaction temperature is 60 to 170° C., and the reaction is cycled 1 to 5 times.

10. A chitin / chitosan aerogel material composited with biomass calcium carbonate, characterized in that: The aerogel material is prepared by the preparation method described in any one of claims 1 to 9, and has a porous structure and is composed of chitin or chitosan, and the material contains calcium carbonate.

Citation Information

Patent Citations

  • Method for efficiently dissolving chitin and application of chitin

    CN114907577A

Cited By

  • Phytic acid modified biomass-based composite aerogel and preparation method and application thereof

    CN122685977A